Предмет: Алгебра,
автор: denisovroma0970
x(x+3)^2-(x+2)(x^2-2x+4)-2*(x-2)(3x+2)=
Ответы
Автор ответа:
0
х(х+3)²-(х+2)(х²-2х+4)-2•(х-2)(3х+2)=
Тут есть формула (а+b)² = а²+2аb+b²
(x+3)² = x²+2•3•x+3² = x²+6x+9
x(x²+6x+9)-(x+2)(x²-2x+4)-2•(x-2)(3x+2)
x³+6x²+9x-(x³-2x²+4x+2x²-4x+8)-(6x²+4x-12x-8)
x³+6x²+9x-x³+2x²-4x-2x²+4x-8-6x²-4x+12x+8 x³-x³+6x²+2x²-2x²-6x²+9x-4x+4x-4x+12x-8+8 = 17x
Надеюсь все правильно, удачи :)
Похожие вопросы
Предмет: Другие предметы,
автор: danil23022
Предмет: Другие предметы,
автор: Vlada03122003
Предмет: Русский язык,
автор: irina02022002
Предмет: Геометрия,
автор: denliverpool95
Предмет: Математика,
автор: karinatrohimenk